Effectiveness of a Planned Teaching Program on the Knowledge of Staff Nurses with Regard to the Nutritional Requirements of Patients with Chronic Kidney Disease - Fernandes, Sarita Telma; Dsilva, Fatima; Dsouza, Sushma Marita (Journal of Health and Allied Sciences NU, 2021)
Objective This study was done to evaluate the effectiveness of a planned teaching program on the knowledge of staff nurses with regard to the nutritional requirements of patients with chronic kidney disease.Methods Uncontrolled before-and-after study was conducted among staff nurses of a hospital. Convenient sampling was used to select the participants. Pretest knowledge was assessed using a structured questionnaire among staff nurses. After the pretest, the experimental group was administered a planned teaching program for 60 minutes. On the 7th, 14th, 21st, and 28th day the posttests were conducted by delivering the same tool to determine the posttest level of knowledge after the administration of the planned teaching program.Results The staff nurses’ pretest knowledge scores reveal that the majority (77.5%) had an average knowledge level and 10% had poor knowledge levels. The effectiveness of the planned teaching program showed that the mean pretest knowledge score of the staff nurses (x̄ 1=16.10) was significantly lower than the mean posttest knowledge scores of the participants (x̄ 2 = 20.78, x̄ 3 = 24.35, x̄ 4 = 24.20, and x̄ 5 = 28.75).Conclusion In this study, the planned teaching program was found to be efficient on the knowledge level of staff nurses regarding the nutritional requirements of patients with chronic kidney disease.
Keywords: chronic kidney disease; staff nurses; knowledge; planned teaching program